2021
DOI: 10.1080/03019233.2021.1958632
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic activity of FeO in CaO–SiO2–MnO–FeO–MgO molten slags

Abstract: To understand the thermodynamic characteristics of the melting process for high manganese twinning-induced plasticity steel, the activity coefficient of FeO in molten slag of MnO-CaO-SiO 2 -FeO-MgO slag system with up to 52 mass% MnO was measured at 1450°C by the experiments of the iron equilibrium between liquid silver and molten slag under the mixed gas atmosphere of CO, CO 2 and Ar. The effects of MnO, FeO and the basicity on the activity coefficient of FeO in molten slag were discussed. The relationships b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…The experimental device and the experimental process used in this research have been reported in detail in the determination of MnO and FeO activity. 18,19) But in order to measure the temperature of the melt in the crucible more accurately, the thermocouple was moved from the bottom of the crucible into the corundum crucible. The number of reaction crucibles in the corundum crucible was increased to six.…”
Section: Methodsmentioning
confidence: 99%
“…The experimental device and the experimental process used in this research have been reported in detail in the determination of MnO and FeO activity. 18,19) But in order to measure the temperature of the melt in the crucible more accurately, the thermocouple was moved from the bottom of the crucible into the corundum crucible. The number of reaction crucibles in the corundum crucible was increased to six.…”
Section: Methodsmentioning
confidence: 99%